Fused Nickel(II) Porphyrins—Sensing of Toxic Anions and Selected Metal Ions Through Supramolecular Interactions - Dar, Tawseef Ahmad; Sankar, Muniappan (Frontiers in Chemistry, 2020)
Ni(II) porphyrins having fused –NH group were synthesized and characterized by various spectroscopic techniques. The fused porphyrins 1 and 2 were used to detect species of opposite polarity. 1 was used to sense toxic anions viz. cyanide and fluoride ions whereas 2 was used for detecting some selective metal ions including toxic mercury(II) ions. 1 is having acidic –NH proton, which detects anions via hydrogen bonding interactions followed by anion-induced deprotonation. On the other hand, 2 senses the metal species via weak charge transfer interactions from oxygen atom of the formyl group to the added metal ions. The limit of detection was calculated in case of 1 as 2.13 and 3.15 ppm for cyanide and fluoride ions, respectively. Similarly, the detection limit was found to be 0.930, 2.231, and 0.718 ppm for Cu(II), Fe(III), and Hg(II) ions, respectively, for probe 2. The probes were recovered and reused for several cycles.